Green synthesis and antimicrobial activities of Arthospira platensis zinc oxide nanoparticles - Kanika K; Medha Durgapal; Aradhana K; Mukesh Kumar (Environment Conservation Journal)
Overuse of antibiotics poses a significant public health risk, highlighting the need for novel chemicals to prevent infection spread. A simple green approach has been devised to synthesize zinc oxide nanoparticles (ZnO NPs) from the methanolic concentrate of Arthrospira platensis as a stabilizing and reducing agent. In this work, metabolites found in the cell filtrate of microalga, Arthrospira platensis (Class: Cyanophyceae), were successfully utilized to create zinc oxide nanoparticles. Characterization of ZnO-NPs was done by scanning electron microscopy (SEM), energy dispersive spectroscopy, Fourier transform infrared, UV-vis spectroscopy, and X-ray diffraction. The results obtained from analyses show the activities of biosynthesized ZnO-NPs were dose-dependent. Inhibition zones of 15.56-25.46 mm, 14.33-24.56 mm, 14.02-22.01 mm, and 23.06-30.26 mm at 1 mg/ml, 2 mg/ml, 3 mg/ml, and 4 mg/ml against Staphylococcus aureus MTCC-7443, Escherichia coli 443, Klebsiella pneumoniae 4031, and Candida albicans 227, respectively, were observed. The present study postulates that green ZnO NPs are a safe alternative to synthetic antimicrobials with potential use in biomedical fields.